2021
DOI: 10.21203/rs.3.rs-144736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Roles of Emotional Intelligence, Neuroticism, and Academic Stress on the Relationship Between Psychological Distress and Burnout in Medical Students

Abstract: Background: Stress and burnout commonly threaten the mental health of medical students in Malaysia and elsewhere. This study aimed to explore the interrelations of psychological distress, emotional intelligence, personality traits, academic stress, and burnout among medical students. A cross-sectional study was conducted with 241 medical students. Validated questionnaires were administered to measure burnout, psychological distress, emotional intelligence, personality traits, and academic stress, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Bar-On et al (2006) found that higher than average intellectual skills are more successful in coping with environmental and psychological pressure situations. EI indicated a direct effect to reduce the burnout level among the students during stressful environments; consequently, a high level of EI was significantly correlated with the performance of students (Yusoff et al, 2021). It is reasonably acceptable that several studies explored the relationship between EI on the work outcomes of nurses (Ioannidou and Konstantikaki, 2008;Alonazi, 2020;Mo et al, 2020).…”
Section: Emotional Intelligence Work Stress Burnout and Performancementioning
confidence: 99%
“…Bar-On et al (2006) found that higher than average intellectual skills are more successful in coping with environmental and psychological pressure situations. EI indicated a direct effect to reduce the burnout level among the students during stressful environments; consequently, a high level of EI was significantly correlated with the performance of students (Yusoff et al, 2021). It is reasonably acceptable that several studies explored the relationship between EI on the work outcomes of nurses (Ioannidou and Konstantikaki, 2008;Alonazi, 2020;Mo et al, 2020).…”
Section: Emotional Intelligence Work Stress Burnout and Performancementioning
confidence: 99%
“…In brief, this review found common suggestions such as that future research should consider varied (Abdollahi et al, 2022;Cornelius & Ng, 2019;Othman et al, 2017;Yusoff et al, 2021), larger samples (Bhagat et al, 2016;Bhagat et al, 2019;Chung et al, 2019;Cornelius & Ng, 2019;Othman et al, 2017;Sam et al, 2022;Yusof et al, 2016) for the reason that single institution studies commonly has low generalisability (Abdollahi et al, 2022;Bhagat et al, 2016;Sam et al, 2022;Toh et al, 2022;Yew Shen et al, 2022). Also, this review also found 18 studies to have employed cross-sectional method in which a single population was observed at one point in time (Wang & Cheng, 2020).…”
Section: Gaps and Limitations Of The Current Literature Investigating...mentioning
confidence: 99%
“…Summarily, this review has found personality traits to have an influence on pathological online use (Chung et al, 2019;Klobas et al, 2018), students' academic performance (Bhagat et al, 2016;Bhagat et al, 2019) and student's online social usage motivation (Naqshbandi et al, 2017;Ali et al, 2016), student's coping strategies (Sam et al, 2022;Zainah et al, 2019), language learning (Zarina et al, 2019), students level of stress (Toh et al, 2022;Yusof et al, 2016;Yusoff et al, 2021), general anxiety, social anxiety (Abdollahi et al, 2022), burnout level (Yusoff et al, 2021), and symptoms of depression during times of crises (Yusoff et al, 2013;Zainah et al, 2019), neuronal signature of self-consciousness (Hassan et al, 2016), happiness (Tan et al, 2018), and other addictive behaviors such as smoking method preference (Yew et al, 2022), smartphone addiction (Lei et al, 2020), and internet addiction (Othman et al, 2017) which tends to lead to psychological problems (Lei et al, 2020;Yusoff et al, 2021) such as depression (Lei et al, 2020).…”
Section: The Effects Of Personality Traits To University Students In ...mentioning
confidence: 99%
See 2 more Smart Citations